A Methodological Evaluation of the Polish Land Administration System Using the Fit‑For‑Purpose Approach - Dawidowicz, Agnieszka; Zysk, Elżbieta; Źróbek, Ryszard (Geomatics and Environmental Engineering, 2020)
In the past fifteen years, many countries have been making intensive preparations towards the creation of a modern Land Administration System (LAS). These systems are a part of multi‑functional spatial data infrastructure (SDI) which supports land administration. These efforts are complex since the harmonization of spatial data from various independent databases requires significant funding and time. In Poland, national LAS referred to as the Integrated Real Estate Information System (IREIS) has been developed since 2013. In light of the above, this article aims to methodologically determine whether the Polish land administration system meets fit‑for‑purpose criteria. The research approach takes into account the following criteria in the assessment of the Polish LAS: focus on the purpose, flexibility, ability to cover land tenure and land use, affordability, reliability in terms of information, attainability, and upgradeability with regard to incremental improvement. These criteria were estimated in three panels: spatial framework, legal framework, institutional framework. The results of our research indicate that the IREIS project has achieved global standards and is fit for purpose and they can be used to monitor the further development of the ZSIN.